2020
DOI: 10.1002/mgg3.1171
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of del(GJB6‐D13S1830) and del(GJB6‐D13S1834) deletions in a large cohort with hearing loss: Caveats to interpretation of molecular test results in multiplex families

Abstract: Background Mutations involving the closely linked GJB2 and GJB6 at the DFNB1 locus are a common genetic cause of profound congenital hearing loss in many populations. In some deaf GJB2 heterozygotes, a 309 kb deletion involving the GJB6 has been found to be the cause for hearing loss when inherited in trans to a GJB2 mutation. Methods We screened 2,376 probands from a National DNA Repository of deaf individuals. Results Fifty‐two of 318 heterozygous probands with pathogenic GJB2 sequence variants had a GJB6 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 80 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Six GJB6 large genomic deletions have been found and previously reported, they are: >920kb deletion [114], 179 kb deletion [115], 131 kb deletion [116], del(GJB2-D13S175), del(GJB6-D13S1830) and del(GJB6-D13S1854) [117]. In addition to the six, there was a report of a seventh GJB6 deletion, del(GJB6-D13S1834), in February 2020 [118]. We identified the large genomic deletions, GJB6-D13S1830, and GJB6-D18S1854 as the frequently reported GJB6 variants.…”
Section: Discussionmentioning
confidence: 91%
“…Six GJB6 large genomic deletions have been found and previously reported, they are: >920kb deletion [114], 179 kb deletion [115], 131 kb deletion [116], del(GJB2-D13S175), del(GJB6-D13S1830) and del(GJB6-D13S1854) [117]. In addition to the six, there was a report of a seventh GJB6 deletion, del(GJB6-D13S1834), in February 2020 [118]. We identified the large genomic deletions, GJB6-D13S1830, and GJB6-D18S1854 as the frequently reported GJB6 variants.…”
Section: Discussionmentioning
confidence: 91%
“…Seven large genomic deletions of GJB6 have been previously reported, including >920 kb deletion (Feldmann et al, 2009 ), 179 kb deletion (Tayoun et al, 2016 ), 131 kb deletion (Wilch et al, 2010 ), del( GJB6 -D13S175), del( GJB6 -D13S1830), del( GJB6 -D13S1854; Bliznetz et al, 2017 ) and del( GJB6 -D13S1834; Pandya et al, 2020 ). Homozygous deletion of GJB6 results in severe to profound hearing loss in humans, similar to the mouse model (Teubner et al, 2003 ; Mei et al, 2017 ; Pandya et al, 2020 ). In many cases, the large deletions of GJB6 disrupt a 50 cis-acting element upstream of both genes, which abolishes the expression of GJB2 , and hence is responsible for the phenotype (Rodriguez-Paris and Schrijver, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the large deletions of GJB6 disrupt a 50 cis-acting element upstream of both genes, which abolishes the expression of GJB2 , and hence is responsible for the phenotype (Rodriguez-Paris and Schrijver, 2009 ). A recent study reported the del ( GJB6 -D13S1830) deletion in 16.35% of all GJB2 heterozygotes, which causes more profound hearing loss than those with bi-allelic change in GJB2 (Pandya et al, 2003 , 2020 ; Snoeckx et al, 2005 ). The more severe audiological findings in digenic probands cannot be explained by the sole theory of a putative cis-regulatory element in the deleted region (Pandya et al, 2020 ), suggesting that both GJB6 and GJB2 products may contribute to the hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all affected matrilineal relatives in these families exhibited variable severity, age at onset and audiometric configuration of hearing loss, which suggested that the mitochondrial 12S rRNA mutations were not sufficient to produce enough clinical phenotypes, hence, other modified factors including AmAn, nuclear genes, mitochondrial haplogroups or epigenetic modification may contribute to the deafness expression. Furthermore, mutations in GJB2 [42], GJB3 [43], GJB6 [44] and TRMU [45] were implicated to be associated with hearing impairment. However, the absent of any functional variants in these genes suggested that nuclear modified genes may not play active roles in the clinical expression of deafness-associated 12S rRNA mutations.…”
Section: Discussionmentioning
confidence: 99%